Frustrated Phagocytosis on Micro-Patterned Immune Complexes to Characterize Lysosome Movements in Live Macrophages - Labrousse, Arnaud M.; Meunier, Etienne; Record, Julien; Labernadie, Anna; Beduer, Amélie; Vieu, Christophe; Ben Safta, Thouraya; Maridonneau-Parini, Isabelle (Frontiers in Immunology, 2011)
Lysosome mobilization is a key cellular process in phagocytes for bactericidal activities and trans-matrix migration. The molecular mechanisms that regulate lysosome mobilization are still poorly known. Lysosomes are hard to track as they move towards phagosomes throughout the cell volume. In order to anticipate cell regions where lysosomes are recruited to, human and RAW264.7 macrophages were seeded on surfaces that were micro-patterned with immune complexes (ICs) as 4 µm-side squares. Distances between IC patterns were adapted to optimize cell spreading in order to constrain lysosome movements mostly in 2 dimensions. Fc receptors triggered local frustrated phagocytosis, frustrated phagosomes appeared as rings of F-actin dots around the IC patterns as early as 5 minutes after cells made contact with the substratum. Frustrated phagosomes recruited actin-associated proteins (vinculin, paxillin and gelsolin). The fusion of lysosomes with frustrated phagosomes was shown by the release of beta-hexosaminidase and the recruitment of Lamp-1 to frustrated phagosomes. Lysosomes of RAW264.7 macrophages were labeled with cathepsinD-mCherry to visualize their movements towards frustrated phagosomes. Lysosomes saltatory movements were markedly slowed down compared to cells layered on non-opsonized patterns. In addition, the linearity of the trajectories and the frequency and duration of contacts of lysosomes with frustrated phagosomes were measured.¬¬¬¬¬¬¬¬ Using PP2 we showed that instant velocity, pauses and frequency of lysosome/phagosome contacts were at least in part dependent on Src tyrosine kinases. This experimental set-up is the first step towards deciphering molecular mechanisms which are involved in lysosome movements in the cytoplasm (directionality, docking and fusion) using RNA interference, pharmacological inhibition or mutant expression.